Le blog, nouvel espace littéraire entre tradition et reterritorialisation - Isabelle Escolin-Contensou (Itinéraires)
We consider weblogs as a networking environment when they are used as a means to write literature. We look at their goals, their forms and their aesthetics, as well as their relation to both the world and alterity. In order to establish generic criteria, we study how weblogs have been understood, attacked and defined by readers. We show that weblog as rhizome intends to reterritorialise the literary space and becomes a memory tool.